Circadian variation of F.E.V. in shift workers - Guberan, E. (1969)
Guberan, E., Williams, M. K., Walford, Joan, and Smith, Margaret M. (1969).Brit. J. industr. Med.,26, 121-125. Circadian variation of F.E.V. in shift workers. The one-second forced expiratory volume (F.E.V.(1·0)), the forced vital capacity, and the oral temperature were measured in a group of men working a rotating three-shift system—2 to 10 p.m. one week, 10 p.m. to 6 a.m. the next week, and 6 a.m. to 2 p.m. the third week. The outside air temperature at the London Weather Centre was also obtained. Measurements were made on Mondays and Fridays at the beginning, middle, and end of the shift. The mean F.E.V.(1·0) of 19 normal men showed an increase of 0·15 litre (4·1%) between the beginning and end of both the morning shifts, a mean decrease of some 0·05 litre (1·5%) between the beginning and end of the afternoon shifts, and little change during the night shifts. This circadian variation could not be attributed to industrial fume, smoking or a learning effect. The findings will be of practical importance when F.E.V. is measured in shift workers to determine the effects of toxic substances on ventilatory capacity.